Hermann Hagedorn papers - Hagedorn, Hermann, 1882-1964.
Correspondence, subject files, research materials, and miscellany relating primarily to Hagedorn's biographies of Leonard Wood and William Boyce Thompson. Original materials document Thompson's role in relief work in Russia following the Russian Revolution and in securing diplomatic recognition for the Soviet Union. Includes material on Hagedorn's activities relating to loyalty concerns during World War I especially in relation to his fellow German Americans and the Vigilantes, an organization composed chiefly of patriotic artists and authors.
Correspondents include Charles Fanning Ayer, Newton Diehl Baker, Bernard M. Baruch, Albert Ridgely Brunker, Grenville Clark, George B. Cortelyou, Harvey Cushing, Johnson Hagood, James G. Harbord, Harry S. Howland, Cornelius Kelleher, Frank Ross McCoy, Arthur W. Page, Raymond Robins, Elihu Root, Frank Maximilian Steinhart, Henry L . Stimson, Gertrude Hickman Thompson, William Boyce Thompson, S.M. Williams, and Louisa A. Wood.
Library of Congress Prints and Photographs Division.
Poet and biographer.
Collection material in English, with German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ayer, Charles Fanning, -- 1865-1956 -- Correspondence; Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Baruch, Bernard M. -- 1870-1965 -- Correspondence; Brunker, Albert Ridgely, -- 1883-1959 -- Correspondence; Clark, Grenville, -- 1882-1967 -- Correspondence; Cortelyou, George B. -- 1862-1940 -- Correspondence; Cushing, Harvey, -- 1869-1939 -- Correspondence; Hagood, Johnson, -- 1829-1898 -- Correspondence; Harbord, James G. -- 1866-1947 -- Correspondence; Howland, Harry S. -- Correspondence; Kelleher, Cornelius -- Correspondence; McCoy, Frank Ross, -- 1874-1954 -- Correspondence; Page, Arthur W. -- 1883-1960 -- Correspondence; Robins, Raymond, -- 1873-1954 -- Correspondence; Root, Elihu, -- 1845-1937 -- Correspondence; Steinhart, Frank Maximilian, -- 1864-1938 -- Correspondence; Stimson, Henry L. -- 1867-1950 -- Correspondence; Thompson, Gertrude Hickman, -- 1874- -- Correspondence; Thompson, William Boyce, -- 1869-1930.; Thompson, William Boyce, -- 1869-1930 -- Correspondence; Williams, S. M. -- Correspondence; Wood, Leonard, -- 1860-1927.; Wood, Louisa A. -- Correspondence; Vigilantes (Organization); Allegiance -- United States; German Americans; Patriotism in literature; World War, 1914-1918.; Soviet Union -- Foreign relations -- United States; Soviet Union -- History -- Revolution, 1917-1921 -- Civilian relief; United States -- Foreign relations -- Soviet Union; United States -- Intellectual life -- 1865-1918.; Authors; Biographers; Poets